Нова пам’ятка липицької культури на Тернопільщині - Строцень, Б.С.; Ягодинська, М.О. (Археологічні дослідження в Україні, 2010)
The information is presented on the research of Pronyatyn VI, a new settlement of Lypytska culture discovered in outskirts of Ternopil (Pronyatyn housing estate) at Zarichna Street.